Russell: A very short introduction - Grayling, A.C. (Oxford Oxford university press, 2002)
Bertrand Russell (1872-1970) is one of the most famous and important philosophers of the twentieth century. In this account of his life and work A. C. Grayling introduces both his technical contributions to logic and philosophy, and his wide-ranging views on education, politics, war, and sexual morality. Russell is credited with being one of the prime movers of Analytic Philosophy, and with having played a part in the revolution in social attitudes witnessed throughout the twentieth-century world. This introduction gives a clear survey of Russell's achievements across their whole